The effect of the coating process thermal cycle on mechanical properties of AA6061-T6 used for load-carrying elements of a space instrument: a case study - Barciński, Tomasz; Kosturek, Robert; Kowalski, Tomasz; Bzowski, Maciej; Wawrzaszek, Roman; Karol Mostowy; Baran, Jędrzej; Daukszo, Maciej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Components used for the structure of the GLObal Solar Wind Structure experiment in the NASA Interstellar Mapping and Acceleration Probe space mission, made of AA6061-T6 alloy, are subjected to the coating process, where the temperature affects its mechanical properties. This paper aims to examine the impact of the coating thermal cycle on the mechanical properties of AA6061-T6 alloy, which is the load-carrying material in a spaceborne instrument. As a part of the manufacturing process, the parts made of AA6061-T6 are subjected to a coating process at a temperature of about 220◦C for a time longer than 1 hour. This treatment modifies the mechanical properties of the alloy. To evaluate the consequences of this change for spaceborne components, mechanical testing, and numerical simulation were conducted. It was found that as a result of the coating process, the reduction in AA6061-T6 yield strength is about 16%, which entails a decrease in the margins of safety by 25% at its maximum.